2020
DOI: 10.1039/d0cc05728b
|View full text |Cite
|
Sign up to set email alerts
|

Porous Li-MOF as a solid-state electrolyte: exploration of lithium ion conductivity through bio-inspired ionic channels

Abstract: A rarely porous Li-MOF (Li-AOIA) with surface area of 605 m2/g was employed for the formation of an emerging class of solvent free, solid electrolytes. Infiltration of LiBF4 into Li-AOIA...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…It is worth mentioning that the there is no obvious coordinating interaction between TFSI À and Li + ,i ndicating TFSI À are fully disassociated from Li + ,f orming a" salt in ligand" crystal. [19] Thes ingle crystal of the DMOAa nd LiTFSI mixture at the molar ratio of 1:1w as not obtained, but the counterpart single crystal of DMOAa nd LiFSI (1:1, molar ratio) was successfully obtained instead. As shown in Figure 3d the electrostatic interaction between cations and anions.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the there is no obvious coordinating interaction between TFSI À and Li + ,i ndicating TFSI À are fully disassociated from Li + ,f orming a" salt in ligand" crystal. [19] Thes ingle crystal of the DMOAa nd LiTFSI mixture at the molar ratio of 1:1w as not obtained, but the counterpart single crystal of DMOAa nd LiFSI (1:1, molar ratio) was successfully obtained instead. As shown in Figure 3d the electrostatic interaction between cations and anions.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the there is no obvious coordinating interaction between TFSI À and Li + ,i ndicating TFSI À are fully disassociated from Li + ,f orming a" salt in ligand" crystal. [19] Thes ingle crystal of the DMOAa nd LiTFSI mixture at the molar ratio of 1:1w as not obtained, but the counterpart single crystal of DMOAa nd LiFSI (1:1, molar ratio) was successfully obtained instead. As shown in Figure 3d…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Nath et al 55 reported a neutral Li-MOF, Li-AOIA ((Li 2 (H 2 AOIA)(EtOH) 2 )•H 2 O), which has potential to be a good conductor for Li + . The structure of Li-AOIA and the coordination of lithium in it are shown in Fig.…”
Section: Neat Mofs As Li-ion Conductorsmentioning
confidence: 99%
“…(h) Tetrahedral coordination of the Li(I) center in Li-AOIA with ethanol coordination. (i) Arrhenius plot and the E a of Li-AOIA@BF 4 55. Copyright 2020, Royal Society of Chemistry.…”
mentioning
confidence: 99%